In vitro propagation and synseed mediated short-term conservation of Scutellaria alpina L. and Scutellaria altissima L. - Zakaria, Ibrahim Alhassan; Sherman, Samantha; Vaidya, Brajesh; Joshee, Nirmal (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2020)
Nodal explants of medicinal Scutellaria alpina L. and Scutellaria altissima L were studies for in vitro adventitious shoot induction, rooting, acclimatization and synseed production. Shoot induction was studied using Murashige and Skoog medium supplemented with four cytokinins individually in combination with one of the two auxins, naphthalene acetic acid or 2,4-dichlorophenoxyacetic acid. In both species, highest number of shoots were induced in the treatment containing 10µM 6-benzylaminopurine and 0.1µM naphthalene acetic acid. Short- term conservation of 0.2-0.3 mm long nodal explants with axillary buds was tested by forming synthetic seeds and storing at 4-±2 oC for up to eight weeks. Optimization of synseed production was done by testing five concentrations of sodium alginate and two concentrations of calcium chloride, allowing 30 min for polymerization. For S. alpina, synseeds prepared by combining 3 % sodium alginate and 100 mM calcium chloride and for S. altissima combining 3.5 % sodium alginate and 100 mM calcium chloride resulted in 100 % and 75 % regeneration of explants, after three weeks of culture on Murashige and Skoog medium, respectively. Activated charcoal in the rooting medium increased root number in regenerated plants. Elongated shoots were rooted, acclimatized and successfully transferred to the greenhouse. These plants were acclimatized and established ex vitro that were morphologically identical to the mother plants. Index terms: Conservation; encapsulation; medicinal plant; Skullcap; synthetic seed.